Indivisible : restoring faith, family, and freedom before it's too late - Robison, James, frey50; Richards, Jay Wesley, 1967- (New York, N.Y. : FaithWords, 2012)
"A book, geared towards conservative Christians with massappeal, that connects biblical principles with practical politics to have a lasting impact on our culture"--Provided by the publisher.
Principles, policies, and prayer -- What is freedom? -- The law is written on the heart, stone, and parchment -- God in public -- Bearing the sword -- How big is too big? -- Choose life -- A man shall cling to his wife -- It takes a family -- Train up a child in the way he should go -- Culture matters -- Am I my brother's keeper? -- A place to call our own -- Free to win-win -- Going global -- Crossing the border -- All men are created equal -- Be fruitful -- Have dominion -- Till it and keep it -- Conclusion : living within the truth.
Keywords: Christianity and politics -- United States; Christian conservatism -- United States; Christianity and culture -- United States; Christianity and politics -- United States; Conservatism -- United States